How to measure anything in cybersecurity risk - Hubbard, Douglas W., 1962-; Seiersen, Richard, 1967- (Hoboken, New Jersey : Wiley, 2023)
A start-to-finish guide for realistically measuring cybersecurity risk In the newly revised How to Measure Anything in Cybersecurity Risk, Second Edition, a pioneering information security professional and a leader in quantitative analysis methods delivers yet another eye-opening text applying the quantitative language of risk analysis to cybersecurity. In the book, the authors demonstrate how to quantify uncertainty and shed light on how to measure seemingly intangible goals. It's a practical guide to improving risk assessment with a straightforward and simple framework. Advanced methods and detailed advice for a variety of use cases round out the book, which also includes: A new "Rapid Risk Audit" for a first quick quantitative risk assessment. New research on the real impact of reputation damage New Bayesian examples for assessing risk with little data New material on simple measurement and estimation, pseudo-random number generators, and advice on combining expert opinion Dispelling long-held beliefs and myths about information security, How to Measure Anything in Cybersecurity Risk is an essential roadmap for IT security managers, CFOs, risk and compliance professionals, and even statisticians looking for novel new ways to apply quantitative techniques to cybersecurity.
Answers to Trivia Questions for Calibration Exercise -- Chapter 8 Reducing Uncertainty with Bayesian Methods -- A Brief Introduction to Bayes and Probability Theory -- An Example from Little Data: Does Multifactor Authentication Work? -- Other Ways Bayes Applies -- Notes -- Chapter 9 Some Powerful Methods Based on Bayes -- Computing Frequencies with (Very) Few Data Points: The Beta Distribution -- Decomposing Probabilities with Many Conditions -- Reducing Uncertainty Further and When to Do It -- More Advanced Modeling Considerations -- Wrapping Up Bayes -- Notes
Description based on online resource; title from digital title page (viewed on April 25, 2023).
John Wiley and Sons
Keywords: Cyberterrorism; Cyberspace -- Security measures; Risk management; Risk Management; Cyberterrorisme; Gestion du risque; risk management; BUSINESS & ECONOMICS -- Statistics; COMPUTERS -- Security -- General; Cyberspace -- Security measures; Cyberterrorism; Risk management; Cyberterrorism; Cyberspace -- Security measures; Risk management